Injustice in Education and Human Rights in Papua - SEKAR ASTUTI, OKTAVIANA AYU; HIDAYAH, ALICIA NURUL; SALSABILA, DESVITA KHANSA (International Journal of Law and Legal Ethics, 2025)
The results of this study demonstrate that the Indonesian government has yet to fully implement the mandates of the 1999 Human Rights Law and the 2000 Human Rights Court Law. Although Indonesia possesses a comprehensive legal framework through Law No. 39 of 1999 on Human Rights and Law No. 26 of 2000 on Human Rights Courts, their enforcement in conflict regions such as Papua remains weak and inconsistent. Using a normative juridical approach, this study examines the gap between the ideal principles of human rights protection and the realities of their application in the field. Findings reveal that weak accountability among law enforcement institutions, entrenched impunity, and a dominant militaristic approach have collectively led to the state’s failure to protect civilians, particularly educators. To realize substantive justice, Indonesia must pursue legal and institutional reforms, strengthen the independence of human rights bodies, and adopt a human security paradigm centered on protection and recovery for victims. Transparent law enforcement and continuous human rights education are crucial in restoring trust, rebuilding humanity, and healing the wounded sense of justice in Papua.